Mycophenolate mofetil and daclizumab targeting T lymphocytes in bleomycin-induced experimental scleroderma - Ozgen, M.; Koca, S. S.; Dagli, A. F.; Gundogdu, B.; Ustundag, B.; Isik, A. (Wiley, 2012)
Background. T lymphocytes induce the transformation of fibroblasts into myofibroblasts, the main mediators of fibrogenesis. The inosine 5'-monophosphate dehydrogenase inhibitor mycophenolate mofetil (MMF) and the anti-CD25 monoclonal antibody daclizumab (DCZ) have been reported to suppress the proliferation of T lymphocytes. Aim. To evaluate the preventive effects of MMF and DCZ in early stages of bleomycin (BLM)-induced scleroderma. Methods. This study involved five groups of Balb/c mice (n = 10 per group). Mice in four of the groups were injected subcutaneously (SC) with BLM [ 100 lg/day in 100 lL phosphate-buffered saline (PBS)] for 4 weeks; the remaining (control) group received only 100 lL PBS. Three of the BLM-treated groups also received either intraperitoneal MMF 50 or 150 mg/kg/day, or SC DCZ 100 lg/week. At the end of the fourth week, all mice were killed, and blood and tissue samples were obtained for further analysis. Results. In the BLM-treated group, increases were seen in inflammatory-cell infiltration, a-smooth muscle actin-positive (a-SMA+) fibroblastic cell count, tissue hydroxyproline content, and dermal thickness. Dermal fibrosis was histopathologically prominent. In BLM-treated mice also given MMF or DCZ, inflammatory-cell infiltration, tissue hydroxyproline content and dermal thickness were decreased. In the MMF groups, decreases were also noted in a-SMA+ fibroblastic cell count. Conclusion. In this BLM-induced dermal fibrosis model, MMF and DCZ treatments prevented the development of dermal fibrosis. Further studies are needed to evaluate whether targeting T lymphocytes is effective in resolving pre-existing fibrosis in human scleroderma.
Keywords: Systemic-Sclerosis; Monoclonal-Antibody; Cells; Mechanisms; Interleukin-2; Methotrexate; Receptors; Disease; Alpha; Acid